Spatial distribution and morphological transformation of chromium with coexisting substances in tannery landfill. (December 2021) - Guo, Shan-shan; Tian, Yong-qiang; Wu, Hao; Jin, Xiao-dan; Gan, Long-zhan; Li, Yang; Yang, Jin-yan
Abstract: The prosperity and development of tannery industry have brought about rapid economic growth. However, the tannery landfill without anti-seepage measures in the early stage has generated masses of environmental hazards owing to the lack of awareness in environmental protection. Therefore, it is imperative to pay much attention to the understanding of environmental hazards from tannery waste. In this study, solid samples and groundwater samples were collected from a tannery landfill to study the effect of the characteristic pollutants produced by tanning on chromium distribution with other coexisting substances. The results showed that significant correlations were demonstrated between multiple coexisting substances (total organic carbon, total petroleum hydrocarbons, total nitrogen, Cr, F, Ca, Cu and Pb), indicating the possible same source or they coming from the same tannery production stage. The weights of positive effects and negative effects of coexisting substances on total Cr distribution in the profile decreased in the order: total nitrogen > Cu > Ca > Pb > total organic carbon > F > SO4 2– > Cd, and Ni > Cl > Hg, respectively. Moreover, the simulation of Visual MINTEQ showed that the cations were mainly bound to Cr as CrO4 2−, while the anions were bound to Cr 3+ . This study provided a new perspective on the selection of remediation strategies for Cr-contaminated sites to avoid secondary environmental pollution caused by the release of coexisting heavy metals. Graphical abstract: Image 1 Highlights: Total Cr was significantly correlated with TN and TOC, while Cr(VI) was not. Different coexisting substances made various impacts on total Cr concentration. TN, TOC, Cu, Pb, and Ca had a significant positive effect on total Cr. The cation was bound to Cr as CrO4 2− and the anion was bound to Cr 3+ .